Erectile dysfunction, generalized vascular disease and the long term effects of smoking exposure on arterial properties: time is of the essence. (3rd October 2022) - Ioakeimidis, N; Terentes-Printzios, D; Angelis, A; Rokkas, K; Dima, I; Gourgouli, I; Chatzistamatiou, E; Kalfountzos, D; Tsioufis, C; Vlachopoulos, C
Abstract: Introduction: Erectile dysfunction (ED) is considered an early manifestation of generalized vascular disease and may precede clinically overt cardiovascular disease (CVD) by 2 to 5 years. We examined macrovascular changes according to time of ED onset and the impact of smoking on the severity of penile vascular damage and large artery wall changes. Methods: We measured carotid-femoral pulse wave velocity (PWV), carotid intima media thickness (cIMT), augmentation index (AIx) and brachial flow-mediated dilation (FMD) in 378 males with ED (age: 54±7 years). All participants had no clinical manifestations or a history of atherosclerotic disease. They were assessed using the Sexual Health in Men (SHIM)-5 score for ED severity and the penile colour Doppler ultrasonography after intracavernous injection of prostaglandin E1 for measurement of peak systolic velocity (PSV). Low PSV values indicate impaired penile blood inflow and severe vasculogenic ED. ED duration was defined as the time interval between age at diagnosis and study entry. Results: The study population was divided into three groups according to duration of ED. Group 1: <2 years, Group 2: 2–5 years and Group 3: >5 years. Comparison of various parameters among the three groups using one-way ANOVA or the Kruskal–Wallis test did not demonstrate statistically significant differences in age, prevalence of hypertension, diabetes, smoking, peripheral blood pressure (BP) and metabolic parameters (fasting blood glucose, lipid profile, testosterone levels). Total tobacco cigarette exposure was greater in males with ED duration >5 years (Group 3), compared to Group 2 and 1 patients (23.8 vs 22.5 vs 20.7 pack-years, P<0.01). PWV, AIx and cIMT increased and FMD decreased across the three groups (Figure 1). The three groups had comparable PSV value. We then divided the study population into four subgroups according to tobacco exposure (never smokers; light smokers<20 pack-years, moderate smokers 20–40 pack-years and heavy smokers >40 pack-years). The subgroups have similar age and BP. The three smoking subgroups had significantly higher PWV (P<0.001), AIx (P<0.01), cIMT (P<0.01) and lower FMD (P<0.05) and PSV (P<0.05) compared to never smokers. Post hoc analysis revealed higher PWV, AIx and cIMT and lower FMD in heavy smokers compared to moderate and light smokers (all p<0.05). PSV was similar across the three smoking subgroups. Conclusions: The study shows that longer ED duration is associated with a more pronounced vascular dysfunction and subclinical vascular wall changes and that heavy tobacco cigarette exposure significantly deteriorates macrovascular parameters. Furthermore there was a significant impairment of penile vasculature even in light smokers. These findings may partly explain why the same process that contribute to CVD may cause earlier ED symptoms and imply that smoking cessation should be a premising non pharmacological intervention in men with ED. Funding Acknowledgement: Type of funding sources: None.